2014
DOI: 10.4028/www.scientific.net/kem.616.120
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity and Cathode Properties of LaCoO<sub>3</sub> on Lanthanum Silicate Oxyapatite Electrolyte

Abstract: Chemical reactivity and cathode properties of LaCoO3 were investigated using new oxide ion conductor, lanthanum silicate oxyapatite. The LaCoO3 is found to be good candidate for cathode of the lanthanum silicate oxyapatite solid-electrolyte since no chemical reaction occurred between the LaCoO3 and lanthanum silicate oxyapatite heating at 1273 K for 60 h in air. Based on electrochemical measurements, lower overpotential between the LaCoO3 and lanthanum silicate oxyapatite was confirmed compared to the overpote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Conversely, an oxide electrode or a nickel cermet electrode, which is commonly used in a general SOFC, must be used by considering its reactivity with the LSO electrolyte. It has been reported that the LaCoO 3 perovskite material is available for use as an air electrode, 18) and it has been considered that power generation can be improved based on the selection of the electrode material. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, an oxide electrode or a nickel cermet electrode, which is commonly used in a general SOFC, must be used by considering its reactivity with the LSO electrolyte. It has been reported that the LaCoO 3 perovskite material is available for use as an air electrode, 18) and it has been considered that power generation can be improved based on the selection of the electrode material. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the limitations of ceria in SOFCs are due to the fact that at high temperatures or low oxygen partial pressures ceria exhibits mixed ionic and electronic conductivity [17]. On the other hand, perovskite type oxides conduct only ions, and compounds such as lanthanum cobaltate, LaCoO 3 (LCO), are often used in SOFCs as the cathode material [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The SOFCtype cell was fabricated using yttria-stabilized zirconia (TZ-8Y, Tosoh Corp., Japan), lanthanum cobaltite (LaCoO 3 ) synthesized by a citrate combustion method, 38) and platinum paste (TR-7907, Tanaka Kikinzoku Kougyo, Japan). The three-terminal configuration cell was fabricated by the same procedure used in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“…The three-terminal configuration cell was fabricated by the same procedure used in a previous study. 38) The impedance spectrum of the SOFC-type cell was measured at 1073 K under air using the potentio/galvanostat built-in frequency response analyzer (Reference-600, Gamry Instruments, USA). The frequency ranged from 1 MHz to 0.1 Hz with 10 points per order of magnitude arranged on a logarithmic scale.…”
Section: Methodsmentioning
confidence: 99%